The reproductive cycle of the gelada baboon - Dunbar, RIM; Dunbar, P (Elsevier, 1974)
Changes in the visual appearance of the sexual skins of female Theropithecus gelada associated with different stages of the reproductive cycle and with age are analysed using data from a large sample of females in the wild. Changes associated with the oestrous cycle and with pregnancy and birth are confirmed by a more detailed study of particular individuals. These signals are compared with those reported for other primate species. The behaviour of females during the course of the oestrous cycle is examined and compared with that reported for other species of Papio baboons.